The Effect Of Pyrophyllite Use As Admixture In Light Concrete Bricks’s Mechanical Properties - Retno Anggraini; Ristinah Ristinah; Sugeng P. Budio; Stevanus Rony Soewignyo; Winny Firmaninda (Department of Civil Engineering, Faculty of Engineering, University of Brawijaya, 2013)
Pyrophyllite was extracted from Greek Language, in which pyt means fire and phyllon means leaf or sheet. Otherwise, phylit was found not long after phyllon word, in which the meaning was crack’s sheet. Pyrophyllite is combination of silica alumunium that has chemical formula Al2O3.4SiO2H2O. In this research, testing was conducted for mechanical properties of light concrete brick provided by additional material ”Pyrophyllite stone” as additive. The mechanical properties of light concrete brick consist of compressive strength, porosity, stress and strain curve, and elastic modulus. Testing resultsof the light concrete brick will be compared with that without mix of Pyrophyllite additive.